Biomechanical study of isolated radial head dislocation - Naoki Hayami (2018)
© 2017 The Author(s). Background: Isolated radial head dislocation is a rare injury with an unclear pathomechanism, and the treatment is controversial. The purpose of the present study was to investigate the biomechanical contributions of the annular ligament, quadrate ligament, interosseous membrane, and annular ligament reconstructions to proximal radioulnar joint stability. Methods: Five fresh frozen cadaveric upper extremities were amputated above the elbow and solidly fixed on a customized jig. Radial head dislocation was reproduced by sequential sectioning of ligamentous structures and passive mobility testing. Radial head displacement during mobility testing was measured with an electromagnetic tracking device in three forearm rotation positions. The data were compared among different sectioning stages and between two types of simulated ligamentous reconstruction. Results: Lateral displacement of the radial head significantly increased in the neutral forearm rotation after annular ligament sectioning (46 ± 10%, p < 0.05). After quadrate ligament sectioning, we found significant posterior (67 ± 36%, p < 0.05) and lateral (74 ± 24%, p < 0.01) displacement in neutral forearm rotation and pronation. Significant radial head displacement was found in all directions and in all forearm positions after sequential sectioning of the proximal half of the interosseous membrane. Anatomical annular ligament reconstruction stabilized the proximal radioulnar joint except for anterior laxity in neutral forearm rotation (15 ± 6%, p < 0.05). The radial head with Bell Tawse procedure was significantly displaced in all directions. Conclusion: The direction of radial head instability varied depending on the degree of soft tissue sectioning and specific forearm rotation. Anterior radial head dislocation may involve more severe ligament damage than other types of dislocation. Anatomical annular ligament reconstruction provided multidirectional radial head stability.